Depression and Anxiety among Patients with Epilepsy and Multiple Sclerosis: UAE Comparative Study - Taoufik Alsaadi; Khadija El Hammasi; Tarek M. Shahrour; Mustafa Shakra; Lamya Turkawi; Wassim Nasreddine; Mufeed Raoof (Behavioural Neurology)
Depression and anxiety are highly prevalent in patients with epilepsy (PWE), with prevalence rates ranging from 20% to 55%. The cause of this increased rate is multifactorial. Depression and epilepsy are thought to share the same pathogenic mechanism. Anxiety, on the other hand, seems to have a prevalence rate among PWE comparable to, or even higher than, those reported for depression, and it is closely linked to epilepsy. To test this hypothesis, we screened for depression and anxiety 186 and 160 patients attending the epilepsy and MS clinics, respectively, using standardized screening tools to determine the rates of both depression and anxiety, comparing these rates to 186 age, sex matched controls. Among the three groups, only patients with epilepsy were at increased risk of having depression (OR = 1.9), whereas anxiety was not. This finding could point to the shared pathogenic mechanisms hypothesis between depression and epilepsy.